Crust and upper mantle structure associated with extension in the Woodlark Rift, Papua New Guinea from Rayleigh‐wave tomography. (2nd November 2015) - Jin, Ge; Gaherty, James B.; Abers, Geoffery A.; Kim, Younghee; Eilon, Zachary; Buck, W. Roger
Abstract: The Woodlark seafloor spreading center is propagating westward into the Australian plate near the D'Entrecasteaux Islands (DI), Papua New Guinea, generating an active transition zone from continental rifting to seafloor spreading. From March 2010 to July 2011, we deployed 31 on‐shore and 8 offshore broadband seismic stations around the DI region, to explore the dynamic processes of the lithosphere extension and the exhumation of the high‐pressure terranes exposed on those islands. We measure the multiband (10–60 s) Rayleigh‐wave phase velocities from both ambient noise and earthquake signals. These measurements are then inverted for a three‐dimensional shear‐velocity model for the crust and upper mantle. The results indicate that the lithosphere extension is localized near the rift axis beneath the DI, with a shear‐velocity structure in the upper mantle that is similar to mid‐ocean ridges. Beneath the Kiribisi Basin west of DI, an ultraslow shear‐velocity anomaly (∼4.0 km/s) is observed at shallow mantle depth (30–60 km), which can be interpreted either by the presence of excess partial melt due to slow melt extraction, or by the existence of felsic crustal material buried to mantle depth and not yet exhumed. Key Points: 3‐D shear‐velocity structure of the Woodlark Rift, PNG is retrieved We observed a localized upper‐mantle extension along the Woodlark Rift axis Partial melt and/or felsic rocks may exist in the mantle west of DI